CD4+CD25+ regulatory cells contribute to the regulation of colonic Th2 granulomatous pathology caused by schistosome infection. - Joseph D Turner; Gavin R Jenkins; Karen G Hogg; Sarah A Aynsley; Ross A Paveley; Peter C Cook; Mark C Coles; Adrian P Mountford (PLoS Neglected Tropical Diseases)
Eggs of the helminth Schistosoma mansoni accumulate in the colon following infection and generate Th2-biassed inflammatory granulomas which become down- modulated in size as the infection proceeds to chronicity. However, although CD4+CD25+FoxP3+ regulatory T cells (T(regs)) are known to suppress Th1-mediated colitis, it is not clear whether they control Th2-associated pathologies of the large intestine which characterise several helminth infections. Here we used a novel 3D-multiphoton confocal microscopy approach to visualise and quantify changes in the size and composition of colonic granulomas at the acute and chronic phases of S. mansoni infection. We observed decreased granuloma size, as well as reductions in the abundance of DsRed+ T cells and collagen deposition at 14 weeks (chronic) compared to 8 weeks (acute) post-infection. Th2 cytokine production (i.e. IL-4, IL-5) in the colonic tissue and draining mesenteric lymph node (mLN) decreased during the chronic phase of infection, whilst levels of TGF-β1 increased, co-incident with reduced mLN proliferative responses, granuloma size and fibrosis. The proportion of CD4+CD25+FoxP3+T(regs): CD4+ cells in the mLN increased during chronic disease, while within colonic granulomas there was an approximate 4-fold increase. The proportion of CD4+CD25+FoxP3+T(regs) in the mLN that were CD103+ and CCR5+ also increased indicating an enhanced potential to home to intestinal sites. CD4+CD25+ cells suppressed antigen-specific Th2 mLN cell proliferation in vitro, while their removal during chronic disease resulted in significantly larger granulomas, partial reversal of Th2 hypo-responsiveness and an increase in the number of eosinophils in colonic granulomas. Finally, transfer of schistosome infection-expanded CD4+CD25+T(regs) down-modulated the development of colonic granulomas, including collagen deposition. Therefore, CD4+CD25+FoxP3+T(regs) appear to control Th2 colonic granulomas during chronic infection, and are likely to play a role in containing pathology during intestinal schistosomiasis.